Boesenbergia rotunda: nature’s secret for health, wellness and income generation / Sarah Wahid, Siti Nurul Atikah Abu Samah and Nor Azma Yusuf - Wahid, Sarah; Abu Samah, Siti Nurul Atikah; Yusuf, Nor Azma (Universiti Teknologi MARA, Negeri Sembilan, 2024)
In Malaysia, Boesenbergia rotunda is locally known as ‘Temu kunci’. It is a small herbaceous plant with short, fleshy rhizomes that are aromatic and have a mildly pungent taste. The rhizome is finger look-like appearance; thus, its common English name is fingerroot. Boesenbergia rotunda grows naturally in the teak woods of Central and East Java. It is a native of Java and Sumatra and widely farmed in India, Sri Lanka, South-East Asia (especially in Indonesia, Malaysia, and Thailand), and southern China. It thrives in deep forests and is widespread across its natural area. Boesenbergia rotunda can grows to a height of 15 to 40 cm. The wide, green blade of the leaf’s contrasts with the scarlet sheath to create a striking contrast.